TOXICITY OF METHANOL EXTRACT OF JATROPHA GOSSYPIFOLIA L. (BELLYACHE) TO THE JUVENILES OF CLARIAS GARIEPINUS, (BURCHEL) - I., USMAN J.; M., ABJIT; Y., ABUBAKAR J.; K., DAUDA A.; Y., ALIYU; M., SANI A. (Journal of the Inland Fisheries Society of India, 2021)
Juveniles of Clarias gariepinus (Burchel) of length 15.75 Â± 00.50 cm and weight 14.75 Â± 1.25g were exposed to methanol extract of Jatropha gossypifolia L. at concentrations of 0.00, 3.00, 4.00, 5.00, 6.00 and 7.00 mgl-1 in three replications for 96 hours to determine the acute toxicity. Agitated swimming, loss of balance, ventral resting position, and death were observed as symptoms of toxicosis. Opercular ventilation was significantly higher than the control at P<0.05. A dose dependant significant increase P<0.05 of the opercular beats was observed in the first 48 hours, which decreased with time. The lethal concentration at 96 hours (LC50) was 4.90mgl-1. The use of J. gossypifolia as a means of catching fish should be discouraged considering that the non target organisms may also be affected. Key words: Toxicity, Jatropha gossypifolia, Clarias gariepirus.